Bioactive Peptides from Fermented Foods: Production Approaches, Sources, and Potential Health Benefits - Laryssa Peres Fabbri; Andrea Cavallero; Francesca Vidotto; Morena Gabriele (Foods)
Microbial fermentation is a well-known strategy for enhancing the nutraceutical attributes of foods. Among the fermentation outcomes, bioactive peptides (BAPs), short chains of amino acids resulting from proteolytic activity, are emerging as promising components thanks to their bioactivities. Indeed, BAPs offer numerous health benefits, including antimicrobial, antioxidant, antihypertensive, and anti-inflammatory properties. This review focuses on the production of bioactive peptides during the fermentation process, emphasizing how different microbial strains and fermentation conditions influence the quantity and quality of these peptides. Furthermore, it examines the health benefits of BAPs from fermented foods, highlighting their potential in disease prevention and overall health promotion. Additionally, this review addresses the challenges and future directions in this field. This comprehensive overview underscores the promise of fermented foods as sustainable and potent sources of bioactive peptides, with significant implications for developing functional foods and nutraceuticals.